PENGARUH KOMPETENSI, KOMITMEN ORGANISASI, SKEPTISME PROFESIONAL DAN MOTIVASI PADA KUALITAS AUDIT - Rossita, Ni Made Dian; Sukartha, I Made (E-Jurnal Akuntansi; Vol 20 No 3 (2017), 2017)
One of the auditor's role is audit audit to make sure the resultant financial report according to standard. In addition, a very important role as a government audit is to realize accountability and transparency of financial management in the region. Bad governance (bad management) and poor bureaucracy caused the economic crisis to occur in Indonesia, so public confidence in the government was reduced. In growing and enhancing user confidence in financial statement information the role of a neutral and independent auditor is urgently needed. The findings of the offense measure the quality of the audit with regard to the auditor's knowledge and expertise, the probability of finding violations depends on the auditor's technical capabilities. So that auditors who have the competence, organizational commitment, professional skepticism, and high motivation will produce the appropriate audit report and reflect the quality of good audit. The purpose of this study to prove the influence of competence, organizational commitment, professional skepticism and motivation on audit quality. The BPK RI Office of the Bali Provincial Representative is used as a research site because BPK is a government audit that has the task of examining the management and financial responsibility of the State. With as many as 41 auditors as research samples. Nonprobability sampling is used as a sampling method. Multiple linear regression analysis is used as a technique of analysis. The result shows that competence variable have positive effect on audit quality, organizational commitment variable have positive effect on audit quality, professional skepticism have positive effect on audit quality and motivation variable have positive effect on audit quality. Keywords: Competence, Organizational Commitment, Profesional Skepticism, Motivation, Quality Audit.